Rencana Penjadwalan Pembagian Air Irigasi Daerah Irigasi Paguyaman Kanan Kabupaten Boalemo Provinsi Gorontalo - Nadjamuddin, Dedy Febrianto; Soetopo, Widandi; Sholichin, Moh. (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2014)
Water availability is a major problem to be considered in determining cropping patterns in irrigated areas. Considering the importance of irrigation activities, there should be plan an optimal utilization of water in order to get maximum benefit from the existing water supply according to their function. Irrigation area of paguyaman is planned with two doors intercepts. Irrigation Area Paguyaman on right side, is planned to irrigate 4,176 ha of land where still have potential in the irrigated area expansion. Potential expansion of irrigated area is 1500 ha. Paguyaman Irrigation Area is still in the implementation stage of physical construction. The approach used as the basis arrangement for the water distribution is the approach in terms of a balance between the availability of water to the water requirements for crops. Allocating and distribution of water required in an integrated calculation attended by using a Linear Program.Key words: Optimization, Irrigation Area, Linear Program, Solver.